When the Elderly Turn to Petty Crime: Increasing Elderly Arrest Rates in an Aging Population - Sugie, Naomi F. (International criminal justice review, 2017)
Declines in offending in older age have been consistently observed in nearly every criminological study to date. Because of this, theories that address offending in older life focus exclusively on explaining decreases in crime or “desistance.” However, recent increases in elderly arrest rates in some aging societies provide a unique opportunity to forward theories of older age offending with an empirical touchstone. Using Japan as a case study, this article draws from a social integration perspective to examine whether changes in family and economic integration are associated with increasing arrest rates. Using prefectural fixed-effects models with elderly arrests from 1995 to 2004, the findings suggest that weakened family integration is associated with elderly arrest rates, particularly for petty crimes. This article situates these results within the context of Japan and discusses how social integration and later life offending may be related in aging societies like Japan.